Platelets-induced stiffening and strengthening of ice-templated highly porous alumina scaffolds. (December 2016) - Ghosh, Dipankar; Banda, Mahesh; Kang, Hyungsuk; Dhavale, Nikhil
Abstract: This paper describes the effects of the grain-level anisotropy on the microstructure and uniaxial compressive response of the ice-templated alumina scaffolds. Highly porous ( 80 vol.%) scaffolds were fabricated from alumina powders of equiaxed morphology as well as from powder mixtures containing equiaxed and small amount of platelet particles. Presence of the platelets (diameter 8 μm and thickness 400 nm) led to the formation of the interlamellae bridges, and significantly enhanced the stiffness and compressive strength of the scaffolds. Measured improvement of the mechanical response is rationalized based on the stiffening and strengthening effects exhibited by the intralamella and interlamella platelets. Graphical abstract: